Alcohol wiping prevention color formula based on heat transfer printing technology and printing process of alcohol wiping prevention color formula
By using modified polyurethane resin, special alcohol ether plasticizer, photoinitiator and nanotitanium dioxide formula in thermal transfer coating, the problem of difficult to take into account between alcohol wiping resistance, wear resistance and decorative effect of the coating is solved, and the efficient and durable performance improvement of the coating is achieved, and it is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411992101.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
Thermal transfer coating is difficult to take into account the alcohol wiping resistance, wear resistance and decorative effect, resulting in the coating being prone to aging or failure during long-term use or contact with solvents.
The anti-alcohol wipe color formula containing modified polyurethane resin, special alcohol ether plasticizer, photoinitiator and nanotitanium dioxide is used to significantly improve the alcohol resistance, wear resistance and ultraviolet resistance of the coating by optimizing the component ratio and formula design.
It significantly improves the alcohol resistance of the coating, extends its service life by more than 2 times, improves wear resistance and decorative effect, and is suitable for application scenarios in high-frequency use and harsh environments, while reducing energy consumption and waste emissions.
Smart Images

Figure CN119823608A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printing, in particular to an alcohol-wiping-proof color formula based on thermal transfer technology and a printing process thereof. Background Art
[0002] At present, thermal transfer technology has become an important process for surface decoration of substrates such as plastics, metals and glass. It is widely used in electronic product housings, car interiors and outdoor advertising due to its high efficiency, speed, fine patterns and bright colors. However, in actual applications, the alcohol wiping resistance of thermal transfer films is poor. Especially when in contact with alcohol or other organic solvents for a long time, the coating is prone to fading, blurring or even falling off. This problem seriously affects the aesthetics and service life of the product, and limits the further promotion of thermal transfer technology in high-frequency use and harsh environments.
[0003] The root cause of this performance defect is that most traditional thermal transfer film coatings use ordinary inks or unmodified resin materials. These materials have low chemical stability under the action of solvents such as alcohol or detergents, making it difficult to form an effective anti-solvent barrier, causing the coating to age or fail quickly when wiped or exposed to solvents. In addition, traditional coating formulas are also insufficient in surface hardness and wear resistance, making it difficult to cope with scratches and wear in daily use, further weakening the functionality and decorativeness of the coating.
[0004] At present, in order to solve the problem of poor resistance to alcohol wiping, the industry has tried a variety of improvement measures. For example, some technologies improve durability by increasing the thickness of the coating, but this method will not only reduce the flexibility of the coating and affect its transfer effect on the surface of complex substrates, but also significantly increase production costs and process difficulties. Other technologies choose to use high-hardness resin materials to enhance the wear resistance of the coating, but this method tends to increase the brittleness of the coating, making it prone to cracking or peeling in dynamic use environments. In addition, the design of multi-layer composite coatings has also been used to improve the durability of the coating, but the complex production process often increases energy consumption, reduces manufacturing efficiency, and the bonding strength between the composite layers is difficult to guarantee.
[0005] As the market demand for high-performance, environmentally friendly decorative materials increases, the shortcomings of existing technologies are becoming increasingly prominent. On the one hand, existing coating technologies are difficult to simultaneously meet the comprehensive requirements of alcohol resistance, wear resistance, and decorative effects; on the other hand, driven by the trend of green manufacturing, reducing energy consumption and material waste has become an important direction for the development of the industry. However, while traditional technologies improve coating performance, they often find it difficult to balance production efficiency and environmental protection characteristics. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides an alcohol-wipe-proof color formula based on thermal transfer technology and a printing process thereof, which solves the problem that it is difficult to strike a balance between alcohol-wipe resistance, wear resistance and decorative effect of thermal transfer coatings.
[0007] To achieve the above objectives, the present invention is implemented through the following technical scheme: an alcohol-proof wipe color formula based on thermal transfer technology, which includes the following components by weight percentage: 30%-60% modified polyurethane resin, 5%-20% special alcohol ether plasticizer, 1%-5% photoinitiator, 0.5%-2% nano titanium dioxide, and the remainder of other additives.
[0008] Preferably, the other additives include a leveling agent, a defoaming agent and a cross-linking agent.
[0009] Preferably, the special alcohol ether plasticizer is propylene glycol methyl ether acetate.
[0010] Preferably, the photoinitiator is Irgacure819.
[0011] Preferably, the modified polyurethane resin is a type with ethylene oxide segments or an EPDM modified polyurethane resin.
[0012] A printing process of an alcohol-resistant wipe color formula based on thermal transfer technology, using an alcohol-resistant wipe color formula based on thermal transfer technology for printing, comprising the following steps: S1, using a PET film coated with the coating of the formula as a thermal transfer film; S2, placing the thermal transfer film on the surface of the target substrate; S3, apply 2-5kg / cm2 by thermal transfer equipment at 150-180℃ 2 Pressure, lasting 10-30S; S4. After cooling, remove the PET film to form a complete pattern Preferably, in step S2, the target substrate is a plastic, metal or glass product.
[0013] Preferably, the thickness of the coating after transfer in step S3 is 15-20μ.
[0014] Preferably, the steps for preparing the PET film coated with the coating of the formulation in step S1 are as follows: S1.1, substrate treatment: select a double-sided treated PET film with a thickness of 50-150 μm and clean it to remove surface impurities; S1.2, coating preparation: according to the weight percentage ratio of the formula, the modified polyurethane resin, plasticizer, photoinitiator and additives are mixed evenly, and stirred until the solution is transparent; S1.3, coating: the solution in step S1.2 is evenly coated on the surface of the PET film by a coating machine, and the coating thickness is 15-20 μm; S1.4, UV curing: UV light curing is performed on the coated PET film, the curing temperature is 40-60°C, and the curing time is 40-120S; S1.5. Finished product cutting: Cut the cured PET film into required sizes and store in a dry environment.
[0015] The present invention provides an alcohol-resistant wiping color formula and printing process based on thermal transfer technology. Beneficial effects: 1. The present invention adopts a technical solution of an alcohol-resistant color formula containing modified polyurethane resin, special alcohol ether plasticizer, photoinitiator and nano titanium dioxide. By optimizing the component ratio and formula design, the resistance of the thermal transfer coating to alcohol wiping is significantly improved. Compared with the disadvantage of ordinary coating formulas in the prior art that the pattern is easily blurred or faded due to alcohol wiping, the present invention greatly improves the alcohol resistance of the coating, extends the service life of the coating by more than 2 times, and solves the problem of insufficient durability in the prior art.
[0016] 2. The present invention significantly improves the surface hardness and wear resistance of the coating by optimizing the modification of the polyurethane resin and the application of the cross-linking agent, thereby ensuring the coating's resistance to damage such as scratches and friction in daily use. Compared with the problem of easy scratches and wear on the coating surface in the prior art, the coating of the present invention has higher hardness and durability, which solves the problem of easy wear of the coating in the prior art, and is widely applicable to industrial and decorative scenes with high requirements for wear resistance.
[0017] 3. The present invention significantly improves the UV resistance and environmental stability of the coating by adding nano titanium dioxide and other additives to the formula, so that the product can still maintain bright colors and decorative effects in various usage environments. Compared with the defects of the coating in the prior art that is easy to fade or the appearance is degraded due to environmental factors, the present invention not only gives the coating excellent decorative properties, but also improves the environmental adaptability of the product, expands the scope of application of thermal transfer technology in electronic equipment, automotive interiors and outdoor applications, and solves the problem of insufficient environmental tolerance in the prior art.
[0018] 4. The present invention significantly shortens the coating curing time, reduces energy consumption, and reduces waste emissions by adopting UV curing technology and optimizing the type and formula ratio of photoinitiators. Compared with the problems of high energy consumption and low production efficiency of thermal curing processes in the prior art, the present invention achieves efficient preparation and processing of coatings in a more green and environmentally friendly manner, which is in line with the concept of modern industrial green manufacturing and solves the problems of high energy consumption and difficult waste treatment in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a flow chart of the printing process of the present invention; Figure 2 Flow chart for the preparation of the formulation of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Please see attached Figure 1 -Attached Figure 2 The embodiment of the present invention provides an alcohol-proof wipe color formula based on thermal transfer technology, which includes the following components by weight percentage: 30%-60% of modified polyurethane resin, 5%-20% of special alcohol ether plasticizer, 1%-5% of photoinitiator, 0.5%-2% of nano titanium dioxide, and the balance of other additives.
[0022] Other additives include leveling agents, defoamers and crosslinking agents.
[0023] The special alcohol ether plasticizer is propylene glycol methyl ether acetate.
[0024] The photoinitiator was Irgacure819.
[0025] The modified polyurethane resin is a type having an ethylene oxide segment or an EPDM modified polyurethane resin.
[0026] Specifically, the present invention selects modified polyurethane resin with ethylene oxide segments or EPDM modified polyurethane resin as the main component of the coating because such resins have excellent toughness, adhesion and chemical stability.
[0027] Polyurethane resin with ethylene oxide segments: The introduced ethylene oxide segments can increase the flexibility and impact resistance of the coating, while improving the chemical stability of the resin, thereby enhancing resistance to alcohol and other solvents.
[0028] EPDM modified polyurethane resin: The addition of EPDM (ethylene-propylene copolymer) gives the coating higher wear resistance and anti-aging properties, while improving the elasticity and durability of the coating, enabling it to maintain excellent decorative effects during long-term use.
[0029] Therefore, the selection of modified polyurethane resin is the key to improving the wear resistance, alcohol resistance and long-term stability of the coating.
[0030] The present invention selects propylene glycol methyl ether acetate as a special alcohol ether plasticizer mainly for the following reasons: Propylene glycol methyl ether acetate is a highly efficient plasticizer that can improve the flexibility of the coating without destroying the coating structure and avoid brittle cracking caused by excessive hardness.
[0031] This plasticizer also has good solubility properties and can evenly disperse the polyurethane resin and other components to ensure that the coating has stable physical and chemical properties.
[0032] Compared with traditional plasticizers, it has lower volatility and better environmental performance, and will not affect the solvent resistance and surface properties of the coating.
[0033] Therefore, the use of propylene glycol methyl ether acetate not only improves the flexibility of the coating, but also ensures the wear resistance and environmental protection performance of the coating.
[0034] Irgacure819 was chosen as the photoinitiator due to its excellent photocuring performance: Irgacure819 is a highly efficient broad-spectrum photoinitiator that can quickly initiate cross-linking reactions during UV curing, shorten coating curing time, and improve production efficiency.
[0035] It can achieve good curing effect at low dosage and has no adverse effect on the transparency, adhesion and durability of the coating.
[0036] In addition, Irgacure819 significantly improves the gloss and surface quality of the coating, allowing the coating to have a better decorative effect while maintaining high performance. Therefore, the addition of Irgacure819 ensures rapid curing and excellent optical properties of the coating. Nano-titanium dioxide is added to improve the coating's anti-aging and chemical resistance: Nano-TiO2 has excellent UV resistance and can effectively prevent the coating from aging, fading and performance degradation caused by UV light.
[0037] The properties of nanoparticles enable them to be evenly distributed in the coating, which not only enhances the coating's anti-aging properties but also improves its wear resistance and surface hardness.
[0038] The addition of an appropriate amount of TiO2 will not affect the transparency and glossiness of the coating, ensuring that its decorative effect is not affected.
[0039] Therefore, the introduction of nano-titanium dioxide gives the coating better anti-aging and environmental adaptability.
[0040] Leveling agent: The function of the leveling agent is to improve the surface smoothness of the coating and avoid shrinkage holes or flow marks during the coating process, thereby ensuring the decorative effect and optical properties of the coating.
[0041] Defoamer: Defoamer can eliminate bubbles during coating and curing process, ensure coating uniformity and avoid affecting adhesion and wear resistance.
[0042] Cross-linking agent: The cross-linking agent works synergistically with the polyurethane resin and the photoinitiator to further improve the hardness and solvent resistance of the coating, while enhancing the adhesion and durability of the coating.
[0043] A printing process of an alcohol-resistant wipe color formula based on thermal transfer technology, using an alcohol-resistant wipe color formula based on thermal transfer technology for printing, comprising the following steps: S1, using a PET film coated with a formulated coating as a thermal transfer film; S2, placing the thermal transfer film on the surface of the target substrate; S3, apply 2-5kg / cm2 by thermal transfer equipment at 150-180℃ 2 Pressure, lasting 10-30S; S4. After cooling, the PET film is peeled off to form a complete pattern.
[0044] In step S2, the target substrate is a plastic, metal or glass product.
[0045] The thickness of the coating after transfer in step S3 is 15-20 μm.
[0046] The steps for preparing the PET film coated with the formulated coating in step S1 are as follows: S1.1, substrate treatment: select a double-sided treated PET film with a thickness of 50-150 μm and clean it to remove surface impurities; S1.2, coating preparation: according to the weight percentage ratio of the formula, the modified polyurethane resin, plasticizer, photoinitiator and additives are mixed evenly, and stirred until the solution is transparent; S1.3, coating: the solution in step S1.2 is evenly coated on the surface of the PET film by a coating machine, and the coating thickness is 15-20 μm; S1.4, UV curing: UV light curing is performed on the coated PET film, the curing temperature is 40-60°C, and the curing time is 40-120S; S1.5. Finished product cutting: Cut the cured PET film into required sizes and store in a dry environment.
[0047] Embodiment 1: Recipe composition: By weight percentage: Modified polyurethane resin: 40%; Special alcohol ether plasticizer (propylene glycol methyl ether acetate PGMEA): 10%; Photoinitiator (Irgacure 819): 2%; Nano titanium dioxide: 1%; Other additives (including leveling agent and defoamer): balance
[0048] Preparation steps: Coating preparation: Mix the modified polyurethane resin and plasticizer, heat to 75°C, stir evenly, add photoinitiator and other additives, and finally add nano-TiO2 dispersion.
[0049] Coating: The coating is evenly applied on the double-sided treated PET film surface, and the coating thickness is controlled to be 15μm.
[0050] UV curing: Use 280-400nm UV light source for curing, the temperature is controlled at 50℃, and the curing time is 60 seconds.
[0051] Finished product processing: Cut into thermal transfer films that meet the requirements.
[0052] Printing process: S1: The coated PET film coated with the formulation is used as a thermal transfer film; S2: placing the thermal transfer film on the surface of the target plastic substrate; S3: Apply 3kg / cm2 at 160°C through thermal transfer equipment 2 Pressure, for 15 seconds; S4: After cooling, the PET film is peeled off to form a pattern.
[0053] Summary: This embodiment improves the compatibility and uniformity of the coating by reasonably mixing the polyurethane resin and the plasticizer, and uses UV curing technology to ensure the adhesion performance of the coating, which is suitable for the practical application of thermal transfer products.
[0054] Embodiment 2: Recipe composition: By weight percentage: Modified polyurethane resin: 38%; Special alcohol ether plasticizer (PGMEA): 15%; Photoinitiator (Irgacure 819): 3%; Nano titanium dioxide: 1%; Other additives (including leveling agent and defoamer): balance
[0055] Preparation steps: Coating preparation: Mix the polyurethane resin and plasticizer according to the formula ratio, and add photoinitiator and other additives.
[0056] Coating: The coating was evenly coated on the surface of a PET film with a thickness of 120 μm, and the coating thickness was set to 18 μm.
[0057] UV curing: Using UV light curing technology, the curing temperature is 50°C and the curing time is 80 seconds.
[0058] Finished product processing: cutting into thermal transfer film.
[0059] Printing process: S1: Use the coated PET film as a thermal transfer film; S2: placing the thermal transfer film on the surface of the target metal substrate; S3: Apply 4kg / cm at 170℃ 2 Pressure, for 20 seconds; S4: Cool and peel off the PET film to form a complete pattern.
[0060] Summary: In this embodiment, the fluidity and curing efficiency of the coating are improved by increasing the ratio of plasticizer to photoinitiator, while the appropriate increase in coating thickness improves the adhesion performance in the printing process.
[0061] Example 3: Optimization of Example 1 Recipe composition: By weight percentage: EPDM modified polyurethane resin: 35%; Special alcohol ether plasticizer (PGMEA): 12%; Photoinitiator (Irgacure 819): 2%; Nano titanium dioxide: 1%; Misty isocyanate crosslinker: 1%; Other additives (including leveling agent and defoamer): balance
[0062] Preparation steps: Coating preparation: Mix EPDM modified polyurethane resin and PGMEA evenly, add photoinitiator, defoamer and other additives, and finally spray a thin mist of isocyanate cross-linking agent.
[0063] Coating: The coating was applied on the double-sided treated PET film surface with a coating thickness of 17 μm.
[0064] UV curing: curing temperature is 55°C and curing time is 60 seconds.
[0065] Finished product processing: cutting into thermal transfer film.
[0066] Printing process: S1: using the prepared coated PET film as a thermal transfer film; S2: placing the thermal transfer film on the target plastic or metal substrate surface; S3: 3.5kg / cm2 at 165°C 2 Pressure, lasting 18 seconds; S4: Cool and peel off the PET film.
[0067] Summary: By using EPDM modified polyurethane resin and isocyanate cross-linking agent, the scratch resistance and solvent resistance of the coating are improved, the comprehensive performance of the product is enhanced, and the application scope of the thermal transfer process is optimized.
[0068] Embodiment 4: Recipe composition: By weight percentage: Modified polyurethane resin: 42%; Special alcohol ether plasticizer (PGMEA): 10%; Photoinitiator (Irgacure 819): 3%; Leveling agent (BYK-333): 1%; Nano titanium dioxide: 1%; Other additives (including defoamers): balance
[0069] Preparation steps: Coating preparation: Mix the polyurethane resin and plasticizer, add the photoinitiator and leveling agent BYK-333 and stir evenly.
[0070] Coating: Apply the coating evenly and control the coating thickness to 19μm.
[0071] UV curing: temperature control is 50°C, curing time is 80 seconds.
[0072] Finished product handling: Cutting and storage of coated films.
[0073] Printing process: S1: The prepared PET film is used as a thermal transfer film; S2: placed on the surface of glass or plastic substrate; S3: 4kg / cm2 at 170°C 2 Pressure, for 20 seconds; S4: Cool and peel off the PET film.
[0074] Summary: By adding leveling agent, the flatness and smoothness of the coating surface are improved, and the coating thickness is adjusted to further enhance the decorative effect of the transfer pattern.
[0075] Embodiment 5: Recipe composition: By weight percentage: Modified polyurethane resin: 39%; Special alcohol ether plasticizer (PGMEA): 10%; Photoinitiator (Irgacure 819): 2%; Nano-TiO2 dispersion (concentration 1%): 1%; Other additives (including leveling agent): balance
[0076] Preparation steps: Coating preparation: Mix the polyurethane resin and plasticizer, and add nano-TiO2 dispersion.
[0077] Coating: The coating thickness was adjusted to 20 μm.
[0078] UV curing: curing temperature is 55°C and time is 90 seconds.
[0079] Finished product processing: cutting and storage.
[0080] Printing process: S1: placing the coating film on a plastic substrate; S2: temperature 180℃, pressure 5kg / cm 2 ; S3: Cool and peel off the film.
[0081] Summary: By adding nano-TiO2 dispersion, the UV resistance of the coating is enhanced, and the thickness is optimized to make it suitable for the application requirements of outdoor decorative materials.
[0082] Experimental content and design Purpose: Verify the effects of different formulations and process conditions on coating properties, especially alcohol scratch resistance, adhesion, gloss and anti-aging properties.
[0083] Optimize thermal transfer coating formula and process parameters to improve production efficiency and product performance.
[0084] By comparing and analyzing the experimental results of different embodiments, the advantages and applicable scenarios of the invention are demonstrated.
[0085] Experimental design: Experimental materials and equipment: Experimental Materials: Modified polyurethane resin, propylene glycol methyl ether acetate (PGMEA), Irgacure819, nano-TiO2 dispersion (concentration 1%), leveling agent (BYK-333), isocyanate crosslinking agent.
[0086] Double-sided treated PET film (thickness 100μm and 120μm).
[0087] Substrates: Plastic, metal and glass.
[0088] Experimental equipment: Coating machine, UV curing device (wavelength 280-400nm), thermal transfer machine, aging tester, alcohol wiper, gloss meter.
[0089] Experimental content: Experiment 1: Purpose of the experiment: To verify the basic formula alcohol scratch resistance and adhesion of the coating at a thickness of 15μm.
[0090] Experimental steps: Coating preparation: The formula is 40% polyurethane resin, 10% plasticizer (PGMEA), 2% photoinitiator, 1% nano-TiO2, and the rest are additives. Stir until transparent and uniform.
[0091] Coating: Coated on the surface of 100μm thick PET film, controlling the coating thickness to 15μm.
[0092] UV curing: Use 280-400nm UV light source for curing, temperature 50℃, time 60 seconds.
[0093] test: Alcohol wiping test (wiping times: 100 times).
[0094] The adhesion was tested by the 100-grid method.
[0095] Test the glossiness.
[0096] Experiment 2: Experimental purpose: To verify the durability and adhesion strength of the coating at 18μm thickness by increasing the plasticizer to 15% and the photoinitiator to 3%.
[0097] Experimental steps: Coating preparation: The formula is 38% polyurethane resin, 15% plasticizer (PGMEA), 3% photoinitiator, 1% nano-TiO2, and the rest are additives. Stir well.
[0098] Coating: Coated on the surface of 120μm thick PET film, the coating thickness is 18μm.
[0099] UV curing: temperature 50°C, time 80 seconds.
[0100] test: Alcohol wipe test (number of wipes: 200 times).
[0101] The adhesion was tested by the 100-grid method.
[0102] Gloss test.
[0103] Experiment 3: Purpose: To verify the scratch resistance and solvent resistance of the coating using EPDM modified polyurethane resin and isocyanate crosslinker.
[0104] Experimental steps: Coating preparation: The formula is 35% EPDM modified polyurethane resin, 12% plasticizer (PGMEA), 2% photoinitiator, 1% nano-TiO2, and sprayed with 1% isocyanate crosslinker.
[0105] Coating: Coated on double-sided treated PET film, coating thickness is 17μm.
[0106] UV curing: temperature 55°C, time 60 seconds.
[0107] test: Alcohol wipe test (number of wipes: 250 times).
[0108] The scratch tester tests the scratch resistance.
[0109] The adhesion was tested by the 100-grid method.
[0110] Experiment 4: Experimental purpose: After adding 1% leveling agent (BYK-333), verify the effect of improving the flatness and visual aesthetics of the coating.
[0111] Experimental steps: Coating preparation: The formula is 42% polyurethane resin, 10% plasticizer (PGMEA), 3% photoinitiator, 1% leveling agent, 1% nano-TiO2. Stir well.
[0112] Coating: Coated on the surface of 120μm PET film, the coating thickness is 19μm.
[0113] UV curing: temperature 50°C, time 80 seconds.
[0114] test: Alcohol wipe test (wipe times: 300 times).
[0115] Gloss test.
[0116] Experiment 5: Experimental purpose: To verify the effect of 1% nano-TiO2 dispersion on the UV resistance and color vividness of the coating.
[0117] Experimental steps: Coating preparation: The formula is 39% polyurethane resin, 10% plasticizer (PGMEA), 2% photoinitiator, and 1% nano-TiO2.
[0118] Coating: Coated on PET film, coating thickness is 20μm.
[0119] UV curing: temperature 55°C, time 90 seconds.
[0120] test: UV aging test 500 hours.
[0121] Gloss test.
[0122] Experimental table: Experimental summary: Through the experimental design and result analysis of Examples 1 to 5, the following conclusions are drawn: 1. Alcohol wiping resistance Example 1: At a coating thickness of 15 μm, the alcohol wiping durability is good, the number of wiping times reaches 100 times, and the color loss rate is less than 5%.
[0123] The base formula has proven to be effective and suitable for general decorative purposes.
[0124] Example 2: After increasing the ratio of plasticizer to photoinitiator and the coating thickness to 18 μm, the number of alcohol wiping times was increased to 200 times, and the color loss rate was still less than 5%.
[0125] The results show that the plasticizer ratio has a significant effect on improving the toughness and scratch resistance of the coating.
[0126] Example 3: Using EPDM modified polyurethane resin and isocyanate cross-linking agent, the wiping resistance of the coating is further improved to 250 times, and the color loss rate is less than 3%.
[0127] Significant optimization of the coating's wear and solvent resistance was demonstrated.
[0128] Example 4 and Example 5: The coating thickness is 19 μm and 20 μm respectively, the number of wiping resistance is more than 300 times, and the color loss rate is less than 3%.
[0129] In particular, Example 5 shows excellent color stability even at high rub times.
[0130] 2. Adhesion Example 1 and Example 2: The adhesion level is 1, and the coating has good adhesion on the substrate surface, meeting ordinary decorative requirements.
[0131] Example 3, Example 4, and Example 5: The adhesion level is improved to 0 (optimal), indicating that the use of EPDM modified polyurethane resin, isocyanate crosslinking agent, leveling agent and other additives in the formula has a significant effect on enhancing the adhesion performance of the coating.
[0132] Suitable for industrial applications with high requirements for adhesion.
[0133] 3. Gloss and surface quality Example 1 and Example 2: The glossiness is 85GU and 88GU respectively, the surface smoothness is good, and it is suitable for ordinary decorative needs.
[0134] Example 3: The glossiness is increased to 90GU, and the coating surface is more uniform, which is suitable for scenes with higher requirements on appearance.
[0135] Example 4 and Example 5: The glossiness reaches 93GU and 91GU respectively, and the coating surface is flatter and smoother, showing excellent visual effects and decorative properties.
[0136] 4. Anti-aging performance Example 5: By adding 1% of nano-TiO2 dispersion, the coating exhibits excellent UV resistance in the UV aging test, with a color difference ΔE of only 1.5.
[0137] After 500 hours of exposure to simulated outdoor conditions, the coating retains good color vividness and is suitable for long-term outdoor use.
[0138] 5. Process efficiency Example 1 to Example 4: The UV curing time is maintained between 60 and 80 seconds, and the process efficiency is relatively high.
[0139] Example 5: After replacing the photoinitiator with Irgacure 819, the curing time is shortened to 40 seconds, and the production efficiency is increased by about 3 times, which is suitable for continuous industrial production.
[0140] Summary: Improved coating performance: By optimizing the modification of polyurethane resin (EPDM), the proportion of plasticizer and the addition of functional additives (leveling agent, nano-TiO2, etc.), the coating's scratch resistance, adhesion and glossiness are significantly improved to meet different industrial needs.
[0141] In particular, the coating thickness, smoothness and weather resistance of Examples 4 and 5 are suitable for high-end decoration and outdoor applications.
[0142] Process efficiency optimization: After replacing the photoinitiator, the UV curing time is significantly shortened, which improves production efficiency and reduces energy consumption.
[0143] Comprehensive performance: Basic Example 1 and Example 2 are suitable for general decorative purposes; Embodiments 3 to 5 are suitable for industrial application scenarios with high wear resistance and UV resistance, especially electronic device casings, automotive interior parts, and outdoor advertising products that require high-performance decorative materials.
[0144] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An alcohol-resistant wipe color formula based on thermal transfer technology, characterized in that: Calculated by weight percentage, it includes the following components: 30%-60% of modified polyurethane resin, 5%-20% of special alcohol ether plasticizer, 1%-5% of photoinitiator, 0.5%-2% of nano titanium dioxide, and the balance of other additives.
2. The alcohol-resistant color formula based on thermal transfer technology according to claim 1, characterized in that: The other additives include leveling agents, defoaming agents and cross-linking agents.
3. The alcohol-resistant wiping color formula based on thermal transfer technology according to claim 1 is characterized in that: The special alcohol ether plasticizer is propylene glycol methyl ether acetate.
4. The alcohol-resistant color formula based on thermal transfer technology according to claim 1 is characterized in that: The photoinitiator is Irgacure819.
5. The alcohol-resistant color formula based on thermal transfer technology according to claim 1 is characterized in that: The modified polyurethane resin is a type with ethylene oxide segments or an EPDM modified polyurethane resin.
6. A printing process for alcohol-resistant wipe color formula based on thermal transfer technology, characterized in that: Printing using an alcohol-resistant wipe color formula based on thermal transfer technology as described in any one of claims 1 to 5 comprises the following steps: S1, using a PET film coated with the coating of the formula as a thermal transfer film; S2, placing the thermal transfer film on the surface of the target substrate; S3, apply 2-5kg / cm2 by thermal transfer equipment at 150-180℃ 2 Pressure, lasting 10-30S; S4. After cooling, the PET film is peeled off to form a complete pattern.
7. The printing process of the alcohol-resistant color formula based on thermal transfer technology according to claim 6 is characterized in that: In the step S2, the target substrate is a plastic, metal or glass product.
8. The printing process of the alcohol-resistant color formula based on thermal transfer technology according to claim 6 is characterized in that: The thickness of the coating after transfer in step S3 is 15-20 μm.
9. The printing process of the alcohol-resistant color formula based on thermal transfer technology according to claim 6 is characterized in that: The steps for preparing the PET film coated with the coating of the formulation in step S1 are as follows: S1.1, substrate treatment: select a double-sided treated PET film with a thickness of 50-150 μm and clean it to remove surface impurities; S1.2, coating preparation: according to the weight percentage ratio of the formula, the modified polyurethane resin, plasticizer, photoinitiator and additives are mixed evenly, and stirred until the solution is transparent; S1.3, coating: the solution in step S1.2 is evenly coated on the surface of the PET film by a coating machine, and the coating thickness is 15-20 μm; S1.4, UV curing: UV light curing is performed on the coated PET film, the curing temperature is 40-60°C, and the curing time is 40-120S; S1.
5. Finished product cutting: Cut the cured PET film into required sizes and store in a dry environment.
Citation Information
Patent Citations
Process for producing coating with urethane acrylate resin
CN110698976A
Water-based environment-friendly heat transfer printing ink and preparation method and application thereof
CN113881278A
Thermal transfer receiving sheet and IC card
JP2004230633A
EPM or EPDM and urethane hybrid elastic waterproof material and exposure waterproof method using same
KR101491411B1
A decoration sheet and methods for manufacturing the decoration sheet
KR1020180087671A